Suomen Kansallinen Kasvigeenivaraohjelma suojelutyön tukena 2003-2008 - Veteläinen, Merja (toim.) (MTT, 2008)
Suomen kansallinen kasvigeenivaraohjelma on toiminut suomalaisen kasvigeenivaratyön tukena viisi vuotta. Aktiivisen ohjelman juhlistamiseksi pidettiin juhlaseminaari, jonne kutsuttiin ohjelman toimijoita ja sidosryhmiä. Päivän ohjelma rakentui juhlaseminaarista, jossa kasvigeenivaratyötä valotettiin niin poliittiselta, kulttuuriselta kuin maa- ja puutarhataloussektorilta katsoen; posterinäyttelystä, jossa esiteltiin suomalaista kasvigeenivaratut-kimusta ja säilytystyötä sekä geenivaroja esittelevän Wedlan puutarhan avajaisista. Juhlaseminaarin puhujat painottivat kasvigeenivarojen säilytyksen merkitystä niiden hyödyntämiselle uudenlaisten elintarvikkeiden, lajikkeiden ja tuotteiden kehittelyssä. Ilmastonmuutoksen todettiin tuovan tähän työhön uusia haasteita. Suojelun tukena ovat kansainväliset sopimukset, mutta kattavan muuntelun turvaamiseksi tarvitaan myös kasvigeenivarojen suojelumenetelmiin ja niiden hyödyntämiseen liittyvää tutkimusta. On myös tärkeää herätellä tietoisuutta siitä, että kasviperimä voisi olla osa kulttuurihistoriaamme, jolloin tämän tärkeän resurssin suojelu näkyisi julkisen sektorin toiminnassa ja kansalaisten parissa arvostuksena ja huomioon ottamisena.

The Finnish National Programme for Plant genetic Resources has been functional five years on 2008. To celebrate the active programme an anniversary seminar was held. The programme was composed of a seminar speeches that high-lighted political, cultural and plant industry point of view of the conservation of plant genetic resources in Finland. The poster exhibition presented Finnish research on conservation method development and use of plant genetic resources. The opening ceremony of the demonstration garden "Wendla" gathered the participants to learn about different types of Finnish plant heritage in the Jokioinen estate. The seminar speeches stressed the value of conservation activities to the development of new kinds of food-stuffs, varieties and plant-based products. The challenges of climate change both for conservation and use of plant genetic resources were discussed. The international agreements are the back-bone for the conservation of valuable national plant heritage. However, research on conservation methods and use of plant genetic re-sources are essential to secure a wide diversity of collections. It is also important to in-crease the awareness of the cultural historical values of our plant genetic resources in order guarantee that the public sector dedicates resources for the conservation activities and that the Finnish citizens would appreciate the national plant heritage also in the future years.
Keywords: Ka; kasvigeenivarat; lajikkeet; ilmastonmuutos; suojelu; kulttuurihistoria; plant genetic resources; conservation; varieties; plant heritage; climate change